A comparative study of Shirin and Layla in Khamsa of Nizami Ganjavi - Dastmalchi, Alireza (Pascasarjana UM, 2023)
Lyrical literature is one of the most important and famous types in Persian literature, which is used to express romantic themes and it has been common in various forms such as ghazal and masnavi (double-rhymed verses). The fifth century poet Unsuri’s Vāmiq u ‘Adhrā, Ayyuqi’s Varqa wa Golshāh, Fakhruddin As'ad Gurgani’s Vis and Rāmin are among the famous works in this type of literature. However, this type of literature reached its height in the sixth century in the form of masnavi by Nizami Ganjavi, who among lyrical and romantic poets, according to the masters of speech, no poet has ever achieved his success in storytelling and the evolution of this type of literature. Taking the importance of “Shirin” and “Layla” in the well-known poetries of “Khosrow and Shirin” and “Layla and Majnun” into account, in order to clarify the layers and dimensions of their personality and society on one hand and in attempt to identify the effect of society and parents in forming one’s personality and life on the other hand, the author first presents the summaries of these two stories and then tries to compare and contrast these two elegant characters- according to the characterization of the master and the storyteller of Ganja- and compare their parents and the society among which they were living. May God’s grace abound toward us.